Sexual violence and restorative justice : addressing the justice gap - Keenan, Marie; Zinsstag, Estelle; O'Nolan, Caroline (Oxford : Oxford University Press, 2022)
Concerned by the high attrition rates for sexual crime and the secondary victimization experienced by victims during their participation in the criminal justice system, this book analyses the extent to which restorative justice can address the justice gap that exists in current justice provision. Building on clinical experience and earlier research on sexual crime the authors engage with the complex dynamics and traumatic impact of sexual crime as a critical starting point for their research and examine whether restorative justice can contribute to a more enhanced justice response.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 19, 2022).
Keywords: Sex crimes; Sexual abuse victims; Restorative justice; Criminal justice, Administration of; True Crime; Social services & welfare, criminology